2014
DOI: 10.5539/gjhs.v7n2p304
|View full text |Cite
|
Sign up to set email alerts
|

Trauma in Pregnancy and Its Consequences in Kermanshah, Iran From 2007 to 2010

Abstract: Objective:Nowadays, with decreased mortality of pregnant women by obstetrical causes, trauma has become a leading cause of morbidity and mortality in pregnant women. This study was carried out to determine the frequency of trauma in pregnancy and related causes and selected consequences in pregnant women of Kermanshah, Iran from 2007 to 2010.Methods:In this descriptive-analytical study, all pregnant women who suffered trauma and were admitted to Imam Reza, Taleghani, and Motazedi hospitals located in Kermansha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
(16 reference statements)
1
9
1
Order By: Relevance
“…Due to the fact that the study center is a specialized obstetrics and gynecology hospital, injured patients after motor vehicle accidents are primarily admitted to the emergency departments of hospitals that include multiple disciplines, and this may have reflected to the current study results. However, the present study found increased rate of preterm delivery consistent with the current literature [8,18,19].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Due to the fact that the study center is a specialized obstetrics and gynecology hospital, injured patients after motor vehicle accidents are primarily admitted to the emergency departments of hospitals that include multiple disciplines, and this may have reflected to the current study results. However, the present study found increased rate of preterm delivery consistent with the current literature [8,18,19].…”
Section: Discussionsupporting
confidence: 93%
“…Although studies have demonstrated negative effect of minor trauma on the pregnancy outcomes [5,17], some studies reported no effect of minor trauma on pregnancy outcomes [15]. In the present study, home accidents and domestic violence, as being the causes of minor trauma, were more common in contrast to the findings of the studies in the literature [8,18,19]. Due to the fact that the study center is a specialized obstetrics and gynecology hospital, injured patients after motor vehicle accidents are primarily admitted to the emergency departments of hospitals that include multiple disciplines, and this may have reflected to the current study results.…”
Section: Discussioncontrasting
confidence: 83%
“…Falling may cause traumatic placental injury can result in Maternal-fetal Hemorrhage (MFH) that occurs in 10% to 30% of pregnant trauma patients [18]. Regarding to different causes of trauma in pregnancy, study conducted by Zangene and others [19], showed the most common causes of maternal and fetal injuries were motor vehicle accidents, falling, fighting with husband and maternal stab wound and other traumas (insect bite, explosion, and pollution), and these findings agree with results of the current study.…”
Section: Figure 1: Situation Of Living Births After Maternal Trauma In Pregnancymentioning
confidence: 99%
“…Motor vehicle accidents have been the leading cause of traumatic fetal injury [1][2][3] and previous studies exploring traffic accidents have reported such accidents as the most common cause of trauma during pregnancy (47 ─ 70.4% of the total incidents of trauma in pregnant women). [4][5][6][7] Pregnant women in motor vehicle accidents have a higher risk of preterm labor, placental abruption, and cesarean delivery, and infants born to women injured during pregnancy have a higher risk of preterm birth, low birth weight, and subsequent cerebral palsy. 1,5,8,9 Previous reports conclude that the use of seat belts is an effective tool to protect both pregnant women and their unborn babies.…”
Section: Introductionmentioning
confidence: 99%